Health care for brazilian transvestites and transsexuals: a systematic review protocol (Research, Society and Development, 2022)
The objective of this article is to establish a systematic review protocol to characterize health care for the transvestite and transsexual population in the Unified Health System. The preparation of the protocol was guided by the PRISMA-P checklist and it is registered on the PROSPERO platform, under the code CRD42020188719. The databases SCIELO, LILACS, BVS and PUBMED will be consulted, where empirical studies, with a qualitative or quantitative approach, that deal with health care for transvestites and transsexuals in the Unified Health System will be selected. Screened articles will undergo an assessment of methodological quality and risk of bias, with the help of the Joanna Briggs Institute's critical assessment tools, using a specific checklist for each type of study. The synthesis of the findings will be carried out through the formal narrative and the presentation of tables with summarized data, with the final writing of the review guided by the PRISMA checklist. Based on the scientific evidence, it is intended to present an overview of health care for the transvestite and transsexual population in the Unified Health System. In addition, to point out possible strategies to qualify the political, organizational and attitudinal aspects related to health care for that population.